Direct Metal Layer Forming with Good Adhesion on Porous AAO Films by Electroless Cu Plating. Issue 10 (1st January 2019) - Jinsenji, Makoto; Tajiri, Akihito; Nishimura, Yoshiyuki; Bachman, Mark; Li, Guann-Pyng; Takai, Osamu
Abstract : Porous anodic aluminum oxide (AAO) films have great potential for micro and nano fabrication. Development of metallization techniques for AAO films is necessary for AAO device fabrication. In this work, a process for electroless Cu plating on AAO films was investigated. A quick Pd 2+ removal process after activation improved the adhesion between plated copper (Cu) layer and AAO films. Since the Pd catalyst at the AAO top surface was effectively removed by a complex agent, the plating reaction started approximately 15–20 μm deep in the nanopores. The Cu was continuously deposited to the top of the nanopores and finally covered the AAO surface. The adhesion strength between the Cu films and AAO films measured by the 90° peeling test method was over 0.5 kN/m. Successful electroless Cu plating on AAO is an all-wet chemical batch process that does not require sophisticated fabrication facilities, and can be used as a low-cost metallization process for producing AAO microdevices.